Project-based learning and its potential in physical education: an instructional model inquiry. Issue 1 (2nd January 2021) - Simonton, Kelly L.; Layne, Todd E.; Irwin, Carol C.
ABSTRACT: Innovative Physical Education (PE) instructional and curriculum models have had a modest effect on PE programs in the United States (U.S.). In general, although several evidence-based models have been developed, there has been less adoption within schools. Notwithstanding, science, technology, engineering, arts, and math (STEAM) curriculum and Comprehensive School Physical Activity Programs (CSPAP) have proliferated in many US schools impacting most content areas, including PE. One instructional approach popular in modern education aligning with both programs, is Project-Based Learning (PBL). This article conceptualises current PBL characteristics and its potential in PE. Specifically, we explore how PBL has impacted student learning experiences and the limited research in PE thus far. PE teachers who implement PBL may simultaneously improve student learning and gain a seat at the table with other educational subjects by connecting with schoolwide initiatives. A call for more research on design and implementation of PBL in PE is provided.